PSM / PTA evaluation web management system - Chong, Michael Ka Wai (2013)
Currently, PSM/PTA evaluation management in FSKKP is done manually. As been accepted by the world wide, web-based management system is being used to ease the management process. This project was done to overcome the problem of PSM/PTA evaluation manual management process. PSM/PTA Evaluation Web Management System is web based system that design to manage PSM/PTA management process. This system includes three modules which are of users, student, lecturer, and coordinator. This project use Modified Waterfall Model methodology to implement the development process. PHP and MySQL have been be used as programming language and database respectively for project development. In this project, using web-based will increase the efficiency and reduce human workload in PSM/PTA. This system was tested with unit testing, functionality testing, and user acceptance test. The results show the functionality of the system is passed which users satisfy with the system.